Physical Activity Measured by Accelerometry and its Associations With Cardiac Structure and Vascular Function in Young and Middle‐Aged Adults. Issue 3 (19th March 2015) - Andersson, Charlotte; Lyass, Asya; Larson, Martin G.; Spartano, Nicole L.; Vita, Joseph A.; Benjamin, Emelia J.; Murabito, Joanne M.; Esliger, Dale W.; Blease, Susan J.; Hamburg, Naomi M.; Mitchell, Gary F.; Vasan, Ramachandran S.
Abstract : Background: Physical activity is associated with several health benefits, including lower cardiovascular disease risk. The independent influence of physical activity on cardiac and vascular function in the community, however, has been sparsely investigated. Measures and Results: We related objective measures of moderate‐ to vigorous‐intensity physical activity (MVPA, assessed by accelerometry) to cardiac and vascular indices in 2376 participants of the Framingham Heart Study third generation cohort (54% women, mean age 47 years). Using multivariable regression models, we related MVPA to the following echocardiographic and vascular measures: left ventricular mass, left atrial and aortic root sizes, carotid–femoral pulse wave velocity, augmentation index, and forward pressure wave. Men and women engaged in MVPA 29.9±21.4 and 25.5±19.4 min/day, respectively. Higher values of MVPA (per 10‐minute increment) were associated with lower carotid–femoral pulse wave velocity (estimate −0.53 ms/m; P =0.006) and lower forward pressure wave (estimate −0.23 mm Hg; P =0.03) but were not associated with augmentation index (estimate 0.13%; P =0.25). MVPA was associated positively with loge left ventricular mass (estimate 0.006 loge [g/m 2 ]; P =0.0003), left ventricular wall thickness (estimate 0.07 mm; P =0.0001), and left atrial dimension (estimate 0.10 mm; P =0.01). MVPA also tended to be positively associated with aortic root dimension (estimate 0.05 mm; P =0.052). Associations of MVPA with cardiovascular measures were similar, in general, for bouts lasting <10 versus ≥10 minutes. Conclusions: In our community‐based sample, greater physical activity was associated with lower vascular stiffness but with higher echocardiographic left ventricular mass and left atrial size. These findings suggest complex relations of usual levels of physical activity and cardiovascular remodeling.